Identification and Functional Characterization of a Novel Mutation in the Human Calcium-Sensing Receptor That Co-Segregates With Autosomal-Dominant Hypocalcemia - Rasmussen, Anne Qvist; Jørgensen, Niklas Rye; Schwarz, Peter (Frontiers in Endocrinology, 2018)
The human calcium-sensing receptor (CASR) is the key controller of extracellular Cao2+ homeostasis, and different mutations in the CASR gene have been linked to different calcium diseases, such as familial hypocalciuric hypercalcemia, severe hyperparathyroidism, autosomal-dominant hypocalcemia (ADH), and Bartter’s syndrome type V. In this study, two generations of a family with biochemically and clinically confirmed ADH who suffered severe muscle pain, arthralgia, tetany, abdominal pain, and fatigue were evaluated for mutations in the CASR gene. The study comprises genotyping of all family members, functional characterization of a potential mutant receptor by in vitro analysis related to the wild-type receptor to reveal an association between the genotype and phenotype in the affected family members. The in vitro analysis of functional characteristics includes measurements of inositol trisphosphate accumulation, Ca2+ mobilization in response to [Ca2+]o-stimulation and receptor expression. The results reveal a significant leftward shift of inositol trisphosphate accumulation as a result of the “gain-of-function” mutant receptor and surprisingly a normalization of the response in (Ca2+)i release in the downstream pathway and additionally the maximal response of (Ca2+)i release was significantly decreased compared to the wild type. However, no gross differences were seen in D126V and the D126V/WT CASR dimeric >250 kDa band expression compared to the WT receptor, however, the D126V and D126V/WT CASR immature 140 kDa species appear to have reduced expression compared to the WT receptor. In conclusion, in this study, a family with a clinical diagnosis of ADH in two generations was evaluated to identify a mutation in the CASR gene and reveal an association between genotype and phenotype in the affected family members. The clinical condition was caused by a novel, activating, missense mutation (D126V) in the CASR gene and the in vitro functional characteristics of the mutation co-segregated with their individual phenotype.